Cassini RPWS Dust Observation Near the Janus/Epimetheus Orbit. Issue 6 (28th June 2018) - Ye, S.‐Y.; Kurth, W. S.; Hospodarsky, G. B.; Persoon, A. M.; Gurnett, D. A.; Morooka, M.; Wahlund, J.‐E.; Hsu, H.‐W.; Seiß, M.; Srama, R.
Abstract: During the Ring Grazing orbits near the end of Cassini mission, the spacecraft crossed the equatorial plane near the orbit of Janus/Epimetheus (~2.5  Rs ). This region is populated with dust particles that can be detected by the Radio and Plasma Wave Science (RPWS) instrument via an electric field antenna signal. Analysis of the voltage waveforms recorded on the RPWS antennas provides estimations of the density and size distribution of the dust particles. Measured RPWS profiles, fitted with Lorentzian functions, are shown to be mostly consistent with the Cosmic Dust Analyzer, the dedicated dust instrument on board Cassini. The thickness of the dusty ring varies between 600 and 1, 000 km. The peak location shifts north and south within 100 km of the ring plane, likely a function of the precession phase of Janus orbit. Key Points: Dust particles have been detected near the Janus/Epimetheus orbit by Cassini RPWS and CDA From the RPWS measurements, dust density and size distribution can be derived, which is mostly consistent with CDA results RPWS data indicated that the dusty ring is slightly tilted and slowly precesses as it rotates around Saturn